EFFECT OF ADDING BUTANOL AND ACETONE TO DIESEL FUEL ON EXHAUST GAS EMISSIONS AND SOME ENGINE PERFORMANCE INDICATORS - Abdullah H. S.; N. S. Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the effect of blending two types of alcohol with pure diesel fuel. A 4-cylinder 4- stroke water cooled direct injection (DI) diesel engine was used. An electric dynamometer was connected to the engine to make load by electric heaters; the load on the engine was fixed at full load. The engine was run with two speed levels : 1300 rpm and 1600 rpm. Three types of fuel were used, including blended n- butanol (B) and Acetone(A) mixed with diesel by two levels named by AB15D85 and AB30D70, respectively, and compared with pure diesel fuel (D), which was the baseline. Gas emission was measured by using gas analyzer type AirRex - HG540. Results obtained from the experiment were statistically analyzed and showed that brake thermal Efficiency registered a slight increase of 5.7% when using(AB30D70) compared with base diesel fuel, while the samples (AB30D70, AB15D85) pointed to a slight increase in BSFC by (5.1%and4.4%) respectively when compared with base diesel fuel. The fuel(AB30D70) detected a sharp reduction in both carbon dioxide (CO2) unburned hydrocarbon(HC) and Nitrogen oxides (NOx) by (49.1%,100%, 38%) respectively compared with base diesel fuel